THE INFLUENCE OF INTERACTIONAL TEACHING STYLE ON THE INDEPENDENCE CHARACTERS OF ELEMENTARY SCHOOL STUDENTS - Diah Fitrotul Auliana; Arief Rahman Hakim; Dyah Triwayuningtyas; Yulianti Yulianti; Mohd. Faiz Mohd Yaakob; Diana Wulandari (Al-Bidayah : jurnal pendidikan dasar Islam, 2020)
This study is motivated by teachers' existence in elementary schools (ES), especially in grades IV, V, and VI, because there are still many who use traditional teaching styles. This makes it difficult for students to understand the learning material, and students are less independent in the learning process. A significant influence between teacher teaching styles that are interactional on the independent character of elementary school students. This research uses quantitative methods with data analysis; validity test, reliability test, normality test, simple linear regression test. In contrast, the sample in this study was selected randomly, namely students in grades IV, V, and VI at ES at SDN Ketapanrame 1 Trawas. The data analysis results showed a significant influence between the interactional teaching style of the teacher on the independent character of elementary school students as evidenced by the t-test results of 5.386 with a significant level of .000. The interactional teaching style affected the independent character of students.